THE ROLE OF JOB SATISFACTION IN ENHANCING THE QUALITY OF JOB PERFORMANCE - AN APPLIED STUDY IN IRAQI UNIVERSITIES - Yaamr Abdulateef Hussein (Scholar Express Journals, 2022)
The aim of the research is to know the effect of job satisfaction on the quality of job performance in addition to its actual reality. This study is applied to the employees of Iraqi universities and selects Tikrit University as a model. The researcher used the descriptive analytical method through a questionnaire prepared for this purpose. The most important result of this study is finding a correlation between job satisfaction and job performance quality, in addition to a positive, statistically significant effect of job satisfaction, incentive system, and opportunities for advancement and development on job performance quality. The study recommended paying attention to employees and improving their financial and moral conditions, and the necessity for the university administration to work to enhance job satisfaction for Iraqi university employees because it has an impact on increasing the quality of job performance.
Keywords: : Job Satisfaction; Job Performance; Quality; Incentive System